The linkage of good governance in economic security: an overview - Abdullah, Muhammad Syafiq; Romle, Abd Rahim; Saberi, Nasarina; Muhamad Husin, Nur Khairina; Muhamad Husin, Zatun Najahah (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
This paper scrutinize the linkage of good governance in economic security. Globalisation era led to boarder less world.Thus security of a country threatened not only in military aspect but other than that such as economic security.In achieving the status of the economic security of the country should be based on the knowledge of management, economics, international relations and other important sources of knowledge.In order to understand the sources of success to ensure economic security must understand the configuration of unique resources and skills within state structures according to different social, political and economic stakeholder interests.Thus, every country must implement good governance in their administaration to reduce the risk of threatened economic security.